Structural mechanism for inhibition of PP2A-B56α and oncogenicity by CIP2A - Pavic Karolina; Gupta Nikhil; Omella Judit Domènech; Derua Rita; Aakula Anna; Huhtaniemi Riikka; Määttä Juha A; Höfflin Nico; Okkeri Juha; Wang Zhizhi; Kauko Otto; Varjus Roosa; et al. (Springer Nature, 2025)
The protein phosphatase 2A (PP2A) heterotrimer PP2A-B56α is a human tumour suppressor. However, the molecular mechanisms inhibiting PP2A-B56α in cancer are poorly understood. Here, we report molecular level details and structural mechanisms of PP2A-B56α inhibition by an oncoprotein CIP2A. Upon direct binding to PP2A-B56α trimer, CIP2A displaces the PP2A-A subunit and thereby hijacks both the B56α, and the catalytic PP2Ac subunit to form a CIP2A-B56α-PP2Ac pseudotrimer. Further, CIP2A competes with B56α substrate binding by blocking the LxxIxE-motif substrate binding pocket on B56α. Relevant to oncogenic activity of CIP2A across human cancers, the N-terminal head domain-mediated interaction with B56α stabilizes CIP2A protein. Functionally, CRISPR/Cas9-mediated single amino acid mutagenesis of the head domain blunted MYC expression and MEK phosphorylation, and abrogated triple-negative breast cancer in vivo tumour growth. Collectively, we discover a unique multi-step hijack and mute protein complex regulation mechanism resulting in tumour suppressor PP2A-B56α inhibition. Further, the results unfold a structural determinant for the oncogenic activity of CIP2A, potentially facilitating therapeutic modulation of CIP2A in cancer and other diseases.